Publishing large DNA sequence data in reduced spaces and lasting formats, in paper or PDF - Aguiar, Alexandre Pires (Zootaxa, 2013)
Scientific publications carry a practical moral duty: they must last. Along that line of thinking, some methods are proposed to allow economically and structurally viable publication of DNA sequence data of any size in printed matter and PDFs. The proposal is primarily aimed at contributing for preserving information for the future, while allowing authors to avoid information splitting and complement storage ex situ, that is, in server machines, outside the publication proper. The technique may also help to solve the impasse between the ICZN Code requirement that a new nomen be associated to diagnostic characters for the taxon vs. the phylogenetic definition of taxa, based on cladograms only: sequence data are characters, and can now be easily and comfortably included in taxonomic publications, with direct textual mention to their diagnostic sections. The compression level achieved allows the inclusion of all wanted DNA or RNA sequences in the same printed matter or PDF publications where the sequences are cited and discussed. Reduced font sizes, invisible fonts, and original 2D black & white and color barcodes are illustrated and briefly discussed. The level of data compression achieved can allow each full page of sequence data, or about 5000 characters, to be precisely coded into a color barcode as small as a square of 1.5 mm. A practical example is provided with Taeniogonalos woodorum Smith (Hymenoptera, Trigonalidae). Free software to generate publishable barcodes from txt or FASTA files is provided at www.systaxon.ufes.br/dna.